Thermoluminescent properties of Mn-doped YAP ceramics - Zhydachevskii, Ya.; Suchocki, A.; Berkowski, M. (Видавництво Львівської політехніки, 2012)
The work is devoted to synthesis of Mn-doped YAlO3 (YAP) ceramics by common solid-state reaction and their characterization by photoluminescence and thermoluminescence techniques. An impact of the synthesis conditions on the thermoluminescence (TL) efficiency of the ceramics is analyzed from the point of view of possible application of the material for TL dosimetry of ionizing radiation.
Keywords: YAlO3:Mn ceramics; solid-state synthesis; hermoluminescence; thermoluminescent dosimetry